2023
DOI: 10.1111/jocn.16598
|View full text |Cite
|
Sign up to set email alerts
|

Methodological quality of dignity‐related patient reported outcome measures used in acute hospital settings: A systematic review using the COSMIN methodology

Abstract: Aims and Objective:The aim of this systematic review was to examine the methodological quality of dignity-related patient reported outcome measures (PROMs) used to measure patients' dignity during acute hospitalisation using the Consensus-based Standards for the selection of health Measurement Instruments (COSMIN) methodology for systematic review of PROMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…The resulting 15-item PROM with a 5-factor structure covers the major factors that affect hospitalized older adults' dignity as discussed in the literature, including shared decision-making, HCP-patient communication, patient autonomy, patient privacy and respectful care (Kerr et al, 2020;Nouri et al, 2017;Šaňáková & Čáp, 2019;. Previous systematic reviews of dignity-related PROMs have identified the Inpatient Dignity Scale (IPDS) (Ota et al, 2019) and the Patient Dignity Inventory (PDI) (Chochinov et al, 2008) as the most valid and reliable measures for measuring patients' dignity during acute hospitalization (Fuseini, Redley et al, 2023;Lam et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting 15-item PROM with a 5-factor structure covers the major factors that affect hospitalized older adults' dignity as discussed in the literature, including shared decision-making, HCP-patient communication, patient autonomy, patient privacy and respectful care (Kerr et al, 2020;Nouri et al, 2017;Šaňáková & Čáp, 2019;. Previous systematic reviews of dignity-related PROMs have identified the Inpatient Dignity Scale (IPDS) (Ota et al, 2019) and the Patient Dignity Inventory (PDI) (Chochinov et al, 2008) as the most valid and reliable measures for measuring patients' dignity during acute hospitalization (Fuseini, Redley et al, 2023;Lam et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…that have not been captured by previous dignity-related measures (Karimi et al, 2019; TA B L E 3 Results of exploratory factor analysis. (Fuseini, Redley et al, 2023;Lam et al, 2022). Another unique contribution of the HOADS to the advancement of knowledge on dignity for older adults is the identification of PROM items that are unique to the Ghanaian and African contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, human dignity is unique to each person and is shaped by their relationships with others. Additionally, there is a sense that human dignity is a comprehensive concept that extends beyond the sum of its components 11–13 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there is a sense that human dignity is a comprehensive concept that extends beyond the sum of its components. [11][12][13] Maintaining patient dignity is a fundamental part of providing quality care. 14 Patients recognize dignity as one of the most important aspects of care and make a direct connection between their sense of dignity and respect and the overall quality of their care.…”
mentioning
confidence: 99%